Toward patient involvement and representation in the governance of genomic data archives: deliberative forums with patients in Germany - Apondo, Eric; Mehlis, Katja; Bruns, Andreas; Schickhardt, Christoph; Winkler, Eva C.; Züger, Andrea (Public health genomics, 2025)
Introduction: Although it is generally agreed that the perspectives of patients should be included in decision-making about genomic data, patients rarely have a significant role in the governance of genomic data archives (GDAs). Guidance on the successful implementation of patient involvement (PI) in the governance of GDAs is lacking. This study explores the perspectives of German patients on PI in the governance of GDAs and how these perspectives can be implemented to have an impact on governance. Methods: We conducted 2 online deliberative forums with 26 members of the cancer and rare diseases (RD) communities in Germany. The forums were analyzed qualitatively. The findings were discussed in a follow-up dialogue event with 17 of the participants and 9 members of a GDA (The German Human Genome-Phenome Archive, GHGA) (n = 26). Two patient coresearchers were involved in all phases of the study. Results: Five themes were identified: (a) motivations for PI; (b) concerns about PI; (c) areas of governance in which PI is required; (d) resources necessary for implementation of PI; and (e) the form PI should take. Conclusion: For PI in GDAs to be meaningful, patient perspectives on the specific contextual aspects of GDAs should be actively sought. Patients’ views on representation affect what form of PI they prefer and whether they experience the representation as legitimate. We discuss how the suggestions from the participants of this study were taken up in the governance policy of the GHGA.